The Conception Of Balkanization Within The EastWest Axis - Türkbay, Rezzan Ayhan (European Scientific Journal, ESJ, 2016)
Balkanization, at first glance, is perceived as a conceptualization referring to Balkan geography. This perception is partly valid. Because, the concept is constructed to define the Balkans by the West and it reflects the perception of the West about Balkans. But in the historical process, Balkanization is separated from Balkans and it becomes a way to define any fragmented state or region, especially in the political literature. In a more detailed explanation, the Balkanization conception becomes a division of any multinational state into smaller ethnically homogeneous entities. From this aspect, Balkanization or Balkanist discourse goes beyond the Balkan borders. The main theme of this paper is the construction process of the Balkanization conception.